Dilema Buruh Perempuan Penjemur Padi di Desa Jono Oge - Zaiful, Zaiful; Amir, Andi Mascunra; Bolong, Hadisuddin (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
This study aims to identify the gaps of women rice dryers in meeting the economic needs of the family and to find out the orientation of women rice dryers in planning the future of family members. A qualitative approach was used to describe the phenomenon of women rice dryers from the aspect of socioeconomic relations. Data collection was conducted through observation, interviews and focused discussions. Informants were purposively selected based on their occupational background. The results showed that the socioeconomic gap of women rice dryers from the aspect of social action leads to traditional actions and in its activities must harmonize household chores and work as a rice drying laborer. Control of family finances is controlled by the wife on the grounds that it is to meet unexpected needs, especially the cost of education and anal health. Rice dryers save money in the form of arisan (social gathering) and in general, the form of recreation takes the form of participating in recitation activities and PKK activities. In addition to physical labor, women rice dryers work with patience. This is a necessity to organize the family life of women rice dryers.